PERSEPSI GURU TERHADAP GAYA KEPEMIMPINAN KEPALA SEKOLAH TK DI KECAMATAN LUBUK BEGALUNG KOTA PADANG - Farida , (Universitas Negeri Padang, 2013)
This study aims to determine teachers' perceptions of Kindergarten Principal Leadership Style. This is a descriptive study. The population in this study is 140 teachers. In general, teachers' perceptions Kindergarten Principal Leadership Style in Kecamatan Lubuk Begalung Kota Padang District are in principle leadhership with an average score overall was 2.48. From the research it can be said that principle Leadership Styles of kindergarten kecamatan Lubuk Begalung Padang city is a slight tendency Key word: Principle Leadership Styles